Tools for the Promotion of International Trade in the Eurasian Economic Union Member States: the Case of Kyrgyzstan - K. A. Azhekbarova; A. V. Bondarenko; A. Y. Kozhankov (Финансы: теория и практика, 2018)
The article presents the results of the United Nations Economic Commission for Europe project in Kyrgyzstan: “Reinforcement of national capacity of the trade-support institutions”. Based on these results, the further actions on international trade promotion have been proposed. One of them is a capacity building of state bodies and business in the area of international standards and best practices. It is important to increase the availability of information on the rules and requirements of the government regulation of external economic activity, both within the country and in the partner countries. It is required to provide systematic work with state bodies and businesses in all regions of the Kyrgyz Republic. For this, a permanent Regional Training Centre must be created. The Ryskulbekov Kyrgyz Economic University will become the base for this centre. In close cooperation with the leading universities of the Eurasian Economic Union member states and the countries of Central Asia, it is advisable to expand the region the training centre activity. It is also necessary to envisage the possibility to organise a network model of training programs of the training centre in all countries of the region.